Pembuatan Video Profil UPTD SD Negeri Cinini Kecamatan Haurgeulis Kabupaten Indramayu Sebagai Sarana Promosi - Jajang Riyanto; Susilawati Susilawati (Universitas Pendidikan Indonesia Kampus Serang, 2022)
Advances in digital technology provide many positive influences in the world of education. The rate of information dissemination is growing with various types and provides information quickly as well as profile videos. Making a profile video is one of the author's leading activities in a series of UPI 2021 thematic community service program activities with the theme of building villages through the fields of education and the economy. Dissemination of information about schools that is limited and still conventional by word of mouth is often an obstacle for some parents in knowing the destination school for their children. Unfortunately, some schools did not take a position to have appropriate video profiles. This profile video creation activity aims to make it easier for the community, especially parents, to see the school's profile video and become a digital footprint for schools in promoting schools. The approach taken in this activity is a field approach, where the author tries to collect data and information intensively. This activity involves the Service Technical Implementation Unit of State Elementary School of Cinini in every stage of manufacture. This activity significantly impacted the dissemination of school profile information and boosted the school's popularity. This community service provided help to the community to reach information about the school.